Changes of aqueous humor cytokine and chemokine profiles in femtosecond laser-assisted cataract surgery in comparison to conventional phacoemulsification - Chychko, Lizaveta; Augustin, Victor A.; Son, Hyeck Soo; Schickhardt, Sonja; Daniel, Volker; Khoramnia, Ramin; Auffarth, Gerd U. (Ophthalmology and therapy, 2026)
IntroductionThis study investigates the anterior chamber (AC) inflammation in the early postoperative period after femtosecond laser-assisted cataract surgery (FLACS) in comparison to conventional phacoemulsification (CPS) by quantifying inflammatory and oxidative stress mediators in aqueous humor and correlating findings with clinical data.MethodsIn this prospective single-center study, 80 patients with cataracts were enrolled. Aqueous humor samples were collected from AC after femtosecond laser pretreatment in the FLACS group (40 patients) and at the beginning of standard cataract surgery before the primary incision was created in the CPS group (40 patients, control group). Mediators of postoperative inflammation including TNF-alpha, VEGF, IL-2, IL-1 beta, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, GM-CSF, IFN-gamma, CXCL5/ENA-78, FGF-basic, G-CSF, IL-1-alpha, IL-1-ra, IL-17, CCL2/MCP-1, CCL3/MIP-1a, CCL4/MIP-1b, TPO, TGF-beta-1, TGF-beta-2 and TGF-beta-3 were measured using a multiplex array system. The differences between both groups were analyzed using Mann-Whitney U test.ResultsIn the FLACS group, significantly higher concentrations of IL (interleukin)-4, FGF-basic (fibroblast growth factor) and TGF-ss 2 (Transforming growth factor-beta 2) were detected compared to the CPS group. Conversely, IL-10 levels were significantly higher in the CPS group than in the FLACS group.ConclusionsFLACS triggers a distinct cytokine and growth factor profile in the aqueous humor, including elevated levels of IL-4, IL-12, FGF-basic, and TGF-beta 2 and a reduction in anti-inflammatory IL-10, indicating a shift toward proinflammatory and fibrotic signaling. These molecular changes may underlie immune activation and tissue remodeling not apparent in clinical examination and highlight the need for further studies to evaluate their long-term clinical relevance.